2019
DOI: 10.1109/lcomm.2019.2917677
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Pearson Distance Detection Using a Difference Operator in the Presence of Unknown Varying Offset

Abstract: We consider noisy data transmission channels with unknown scaling and varying offset mismatch. Minimum Pearson distance detection is used in cooperation with a difference operator, which offers immunity to such mismatch. Pair-constrained codes are proposed for unambiguous decoding, where in each codeword certain adjacent symbol pairs must appear at least once. We investigate the cardinality and redundancy of these codes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…For n ≥ 12, the loss is less than 1.5 dB, (for n ≥ 18 the loss is less than 1 dB). Note that the method advocated by Bu et al [10] that aims to solve the same problem has a 3 dB noise penalty, irrespective of the codeword length. For large n, the minimum distance computation is amenable for analysis.…”
Section: B Analysis Of the Error Performancementioning
confidence: 99%
See 1 more Smart Citation
“…For n ≥ 12, the loss is less than 1.5 dB, (for n ≥ 18 the loss is less than 1 dB). Note that the method advocated by Bu et al [10] that aims to solve the same problem has a 3 dB noise penalty, irrespective of the codeword length. For large n, the minimum distance computation is amenable for analysis.…”
Section: B Analysis Of the Error Performancementioning
confidence: 99%
“…They concluded that the redundancy of their scheme is prohibitively large for many applications. Bu and Weber [10] also addressed a channel model where the offset varies within a codeword. They introduced Pearson-distance-based detection in conjunction with a difference operator and a pair-constrained code.…”
mentioning
confidence: 99%